Carfilzomib in relapsed or refractory multiple myeloma patients with early or late relapse following prior therapy: a subgroup analysis of the randomized phase 3 ASPIRE and ENDEAVOR trials - Mateos, Maria-Victoria; Goldschmidt, Hartmut (Hematological oncology, 2018)
We performed analyses of the randomized phase 3 ASPIRE and ENDEAVOR trials to investigate the efficacy of carfilzomib among subgroups of relapsed or refractory multiple myeloma patients who had early or late disease relapse following initiation of the immediately prior therapy. In ASPIRE and ENDEAVOR, patients had received 1 to 3 prior lines of therapy. Patients in ASPIRE received carfilzomib, lenalidomide, and dexamethasone (KRd) or lenalidomide and dexamethasone (Rd), and patients in ENDEAVOR received carfilzomib and dexamethasone (Kd) or bortezomib and dexamethasone (Vd). Patients with relapse ≤1 year after initiating the most recent prior line of therapy were categorized as early relapsers, and patients with relapse after >1 year were categorized as late relapsers. The median progression-free survival (PFS) in ASPIRE for early relapsers was 21.4 months for KRd vs 10.7 months for Rd (hazard ratio [HR]: 0.714; 95% confidence interval [CI]: 0.508-1.004; P = 0.0257), and for late relapsers was 29.7 months for KRd vs 18.2 months for Rd (HR: 0.675; 95% CI: 0.533-0.854; P = 0.0005). The overall response rate (ORR) for early relapsers was 83.2% for KRd vs 54.8% for Rd, and for late relapsers was 89.0% for KRd vs 69.7% for Rd. The median PFS in ENDEAVOR (Kd vs Vd) for early relapsers was 13.9 months vs 5.7 months (HR: 0.598; 95% CI: 0.423-0.846; P = 0.0017), and for late relapsers was 22.2 months vs 10.2 months (HR: 0.486; 95% CI: 0.382-0.620; P < 0.0001). The ORR (Kd vs Vd) for early relapsers was 63.4% vs 49.1% and for late relapsers was 81.8% vs 66.8%. In conclusion, patients with relapsed or refractory multiple myeloma who received carfilzomib-containing regimens had improved PFS and ORR compared with control groups, regardless of whether they had an early or late relapse following the most recent prior therapy.